Patent Prospecting of Technological Alternatives for Swine Hair Management - Fernandes, Jardel Lopes (2024)
The increase in pig farming has driven the growth of industries specializing in slaughtering and processing pork. However, one challenge faced by these industries is the disposal of pig fur, which is often disposed of improperly. This study aims to identify technological alternatives to manage the pig coat, using the patent databases of the World Intellectual Property Organization (WIPO-Patentscope) and the National Institute of Industrial Property (INPI). Employing a unique strategy in both patent databases, it was found that there was a lack of documents in the BPTO database, suggesting an incipient development or lack of concern about the management of this waste in the country. On the other hand, in WIPO-Patentscope, 117 patents related to the use of pig fur were found, and 17 were selected that were suitable for the research. The main alternatives include the production of cosmetics, flour, food additives, paint brushes, power generation, fodder, protein fertilizers, medicine, and various brushes.